Pengaruh Sertifikat Halal Produk Dan Harga Terhadap Kepuasan Konsumen Muslim Pada Dimsum Badzlin Di Kota Dumai - Tengku Mahesa Khalid; Meisya (Al-Hisbah Jurnal Ekonomi Syariah, 2025)
The purpose of this research is to determine the effect of Halal Product Certificates and Prices on the Dimsum Badzlin Dumai business on Muslim Consumer Satisfaction in Dumai City. The method used in this research is a quantitative method. The population in this research is Badzlin Dimsum Consumers. The sampling technique used was Random Sampling which obtained a sample of 106 samples. Then process the data using the SPSS 21.0 For Windows application. The conclusion in this research is that the Halal Certificate variable has a positive effect on consumer satisfaction, then the price variable also has a significant effect on consumer satisfaction. The variables Halal Certificate and Price have a significant influence on consumer satisfaction at Dimsum Badzlin Dumai.